Coupled identification of the hardening behavior laws and GursonTvergaardNeedleman damage parameters - Validation on tear test of 12NiCr6 CT specimen - Mohamed Hadj Miloud; Ibrahim Zidane; Mohammed Mendas (Fracture and Structural Integrity)
This work is devoted to the application of the micromechanical Gurson-Tvergaard-Needleman (GTN) model to study the ductile tearing of 12NiCr6 steel. GTN model is widely used to describe the three stages of ductile tearing: nucleation, growth and the coalescence of micro-voids. A new approach based on the identification of the GTN damage model coupled or not with hardening laws using inverse analysis. After identification, the obtained results show a good agreement between the experimental curve tensile test of an axisymetric notched bar (AN2) and those numerically obtained for GTN model coupled with the hardening laws. In order to validate the identified GTN parameters, a simulation of tear test is conducted on 12 NiCr6 steel CT specimen. The numerical results are compared with experimental results found in the literature and a good agreement is obtained. This identification procedure is more accurate than when the damage parameters are identified independently of the hardening laws.